Assessment of the impact of different factors on changes in carbon intensity of the world economies - Provornaya, Irina V.; Filimonova, Irina V.; Krutilina, Arina D. (Izvestiâ Tomskogo politehničeskogo universiteta. Inžiniring georesursov, 2024)
Relevance. With the restructuring of the economy in the carbon-neutral side, the negative anthropogenic impact can be weakened. It is very likely that there will be a comprehensive analysis of the impact of various climatic accidents in the country and its action to eliminate the risk of carbon dioxide. Moreover, studies in the experience of the peoples of the states make it possible to use their achievements in the field of climate policy in Russia, improve and modernize their advantages from the characteristics of the national economy. Aim. To assess the degree of influence of environmental, climatic and macroeconomic factors on the change in the carbon intensity of the economies of the world. Objects. The parameters of the climate policy of the countries of the world in the field of regulation of carbon dioxide emissions, the subject of the study is the relationship of environmental, climatic and macroeconomic factors with the carbon intensity of the economies of the world. Methods. Econometric method of panel data analysis. Scientific novelty. The paper confirms the hypothesis of the negative impact of one of the main climate policy instruments of the countries of the world (carbon prices) on the carbon intensity of the economy using the construction of the original panel data model. Results. The authors have substantiated a set of factors that affect the carbon intensity of the countries of the world, supplemented by such an indicator as the carbon price, which is one of the main indicators of climate policy development in the country. All factors were divided into two groups (macroeconomic and ecological-climatic) and a database was formed for 24 countries. Using the panel data method, the authors constructed the equation of the dependence of the carbon intensity of the economies of countries on macroeconomic and ecological and climatic factors. The authors tested the hypothesis of the carbon price negative impact on the carbon intensity of the economies of countries. Evaluation of various model specifications allowed us to confirm this hypothesis, which indicates the importance of the climate policy development within each country and the feasibility of introducing new tools to regulate carbon dioxide emissions. It was also determined that GDP, as a general indicator of the development of the entire economy, has the greatest impact on reducing carbon intensity. At the same time, in order to reduce the ratio of carbon dioxide emissions to gross domestic product, it is necessary to pursue a policy of replacing fossil fuels with low-carbon energy sources, but only taking into account the country raw material capabilities and the industry specifics of the economy.